The Thinking Paradigm of Judicial Proof - Wenxiu Fang (Law and Economy, 2023)
With the complexity of social relations, the traditional formal logical thinking cannot solve the hard cases. Inference to the best explanation, a formal logical model of evidential reasoning with proof standards, is applied to this task. The model instructs us to infer from the available evidence to the hypothesis, if the hypothesis correct, which can best explain that evidence. More narrowly, a number of plausible alternative explanations for evidence being observed at trial are generated. Then it enables legal decision-makers to evaluate evidential reasoning by comparing stories on either side of a case, selecting one as the best explanation of the evidence among them. This is a process of elimination. It happily combines falsification, inference and explanation. While traditional logical reasoning is a process of confirmation. Inference to the best explanation has been introduced to law by many scholars, so as to make up for the shortcomings of the logical thinking method. While the article concerns how to apply it in criminal case facts.